The Effect of City/District Minimum Wages on Poverty Levels: A Case Study of the Special Region of Yogyakarta in 2010-2019 - Resafilian Dwi Prayoga; Dyah Titis Kusuma Wardani; Romi Bhakti Hartarto (Journal of Economics Research and Social Sciences, 2022)
Poverty is still a complex economic problem in every country, especially in developing countries like Indonesia. One of Indonesia's provinces with a high poverty rate is the Special Region of Yogyakarta (DIY), which amounted to 11.44% in 2019. This figure is the highest in Java and even higher than the national poverty rate of 9.82%. The high level of poverty is in line with the regional minimum wage of the DIY Province, which is the lowest in Indonesia, which is less than Rp. 1.6 million per month. This study then analyzes the minimum wage at the poverty level in the Province of DIY. The method used in this research is panel data with Fixed Effect Model (FEM) for all districts/cities in DIY Province from 2010-2019. By controlling for variables such as economic growth, education, and health, the results of this study indicate that the minimum wage has a negative effect on poverty levels in the Special Region of Yogyakarta. Therefore, to accelerate poverty reduction in the DIY Province, the provincial and district/city governments must review the minimum wage calculation annually.